2022
DOI: 10.1002/adhm.202202114
|View full text |Cite
|
Sign up to set email alerts
|

Acellularized Uvea Hydrogel as Novel Injectable Platform for Cell‐Based Delivering Treatment of Retinal Degeneration and Optimizing Retinal Organoids Inducible System

Abstract: Replenishing the retina with retinal pigment epithelial (RPE) cells derived from pluripotent stem cells (PSCs) has great promise for treating retinal degenerative diseases, but it is limited by poor cell survival and integration in vivo. Herein, porcine acellular sclera and uvea extracellular matrix (ECM) and their counterpart hydrogels are developed, and their effects on the biological behavior of human induced pluripotent stem cell (hiPSC)‐derived RPE cells (hiPSC‐RPE) and embryoid body (hiPSC‐EB) differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Liu's group recently developed a hydrogel based on the decellularized uvea with excellent cytocompatibility with iPSC‐derived retinal organoids. Animal experiment results indicated that after transplantation, retinal organoids cultured in this hydrogel showed an improved survival rate and were able to restore the vision of retinal degeneration in rats 337 …”
Section: Limitations and Future Perspectivesmentioning
confidence: 95%
See 2 more Smart Citations
“…Liu's group recently developed a hydrogel based on the decellularized uvea with excellent cytocompatibility with iPSC‐derived retinal organoids. Animal experiment results indicated that after transplantation, retinal organoids cultured in this hydrogel showed an improved survival rate and were able to restore the vision of retinal degeneration in rats 337 …”
Section: Limitations and Future Perspectivesmentioning
confidence: 95%
“…Animal experiment results indicated that after transplantation, retinal organoids cultured in this hydrogel showed an improved survival rate and were able to restore the vision of retinal degeneration in rats. 337 Organoids provide unprecedented opportunities to study the development, physiology, and diseases of humans, comprising novel preclinical models with promising application prospects. Organoid models conserve the histological and gene expression properties of native tissue in vivo, and their high similarity to native tissue makes them a valuable addition to cell lines and animal models, which have a high clinical and scientific value.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another significant advantage of polymeric materials as drug carriers is their capacity to sustain drug activity while providing continuous release to the retina. , For instance, injectable hydrogel-delivered cells have demonstrated the promotion of cell survival, differentiation, integration, and repair. , Wang et al devised a local immunotherapy strategy to control retinoblastoma and preserve vision, employing an injectable hydrogel encapsulating GD2-specific CAR-T cells for localized and sustained cell delivery . Another polymeric materials, PLGA, has exhibited continuous release of therapeutic exosomes for a duration of up to 35 days …”
Section: Conventional Nanocarriers For Retinal Diseasementioning
confidence: 99%
“…The RPE is the most amenable to cell therapies among the tissues that are affected in retinal degenerative diseases, since RPE cells do not require the formation of synaptic connections, unlike neuronal cell types [57]. There are several clinical trials underway to test the use of hESC-derived RPE cell therapies, which includes a study showing a good safety profile without ocular inflammation, graft rejection, or tumor formation [70,71]. Furthermore, a recent clinical study carried out in a group of seven patients with Stargardt Disease, a maculopathy, showed safety over a 5-year period, and most of the patients showed increased or stable visual function [72,73].…”
Section: Human Embryonic-like Stem Cells (Hescs)mentioning
confidence: 99%